Dynamic competition, exclusionary and exploitative abuses, and article 102 TFEU: Towards a concept of systemic market power? - Oliver Budzinski; Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2024)
In this paper, we comment on the debate about guidelines for Art. 102 TFEU in the face of the challenges brought by digital ecosystems and abuse of dominance in related markets. We take the perspective of dynamic competition economics and derive four recommendations for the future enforcement of abuse control and related merger control: (i) we advocate to abandon the as-efficient-competitor standard embraced in the late 2000s, (ii) we emphasize the relevance on focusing on exploitative abuses as well as on exclusionary ones, (iii) we suggest to implement a concept of systemic market power as a guideline to enforcement, and (iv) we argue that the same enhanced market power standard should also be applied in the corresponding merger control. While going beyond pure guideline recommendations and focusing on a dynamic-economic view, we are convinced that these steps are necessary to move towards a more effective competition policy towards abuse of digital dominance.
Keywords: K21; L41; L40; L12; L14; L81; L86; 330; abuse of market power; Art. 102 TFEU; digital ecosystems; antitrust; European competition policy; as-efficient-competitor standard; exclusionary abuse; exploitative abuse; dynamic competition; merger control